ALTERITAS KEMANUSIAAN PERANG ISRAEL-HAMAS: PARADIGMA FILSAFAT RELASIONALITAS ARMADA RIYANTO - Yohanes Is Nugroho (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This paper analyses the conflict between Israel and Palestine with the philosophical approach of Armada Riyanto's Philosophy of Relationality. The author emphasizes the dimension of humanity and its alterity in the conflict. From the perspective of Relationality philosophy, it is shown how this war reflects egoism that reduces the value of humanity. The egoism that exists in this conflict, both from Israel and Hamas, overrides the existence of human beings who are also present on the conflicting parties, often sacrificing civilians, including women and children. The concept of human alterity and the meaning of 'the Other', who is an equal subject in relationality, is clarified in relation to this conflict. How the Other or the 'third person' is victimized in this conflict is also a major concern. This paper proposes a more humane resolution to the conflict, which relies not only on political resolutions but also on international awareness of the importance of seeing humans as equal subjects. Empathetic and relationality are key in defusing conflicts and building a paradigm that is more in line with humanity.